The MADS-Box Gene CsSHP Participates in Fruit Maturation and Floral Organ Development in Cucumber - Cheng, Zhihua; Zhuo, Shibin; Liu, Xiaofeng; Che, Gen; Wang, Zhongyi; Gu, Ran; Shen, Junjun; Song, Weiyuan; Zhou, Zhaoyang; Han, Deguo; Zhang, Xiaolan (Frontiers in Plant Science, 2020)
Cucumber is an important vegetable crop bearing fleshy pepo fruit harvested immature. Fruits left unpicked in time during summer production, as well as unfavorable environmental conditions during post-harvest shelf, will cause cucumber fruits to turn yellow and ripen, and thus impair the market value. Identification of maturity-related genes is of great agricultural and economic importance for cucumber production. Here, we isolated and characterized a MADS-box gene, Cucumis sativus SHATTERPROOF (CsSHP) in cucumber. Expression analysis indicated that CsSHP was specifically enriched in reproductive organs including stamens and carpels. Ectopic expression of CsSHP was unable to rescue the indehiscence silique phenotype of shp1 shp2 mutant plant in Arabidopsis. Instead, overexpression of CsSHP resulted in early flowering, precocious phenotypes and capelloid organs in wild-type Arabidopsis. Biochemical analysis indicated that CsSHP directly interacted with cucumber SEPALLATA (SEP) proteins. CsSHP expression increased significantly during the yellowing stage of cucumber ripening, and was induced by exogenous application of abscisic acid (ABA). Therefore, CsSHP may participate in fruit maturation through the ABA pathway and floral organ specification via interaction with CsSEPs to form protein complex in cucumber.